Africa and the Gulf region : blurred boundaries and shifting ties - Abusharaf, Rogaia Mustafa; Eickelman, Dale F., 1942- (Gulf Research Center book series., 2015)
The ties that bind Africa and the Gulf region have deep historical roots that influence both what Braudel called the longue durée and the short-term events of current policy shifts, market-based economic fluctuations, and global and local political vicissitudes. This book, a collaboration of historians, political scientists, development planners, and a biomedical engineer, explores Arabian-African relationships in their many overlapping dimensions. Thus histories constructed from the "bottom up" - records of the everyday activities of commerce, intermarriage, and gender roles - offer an incisi.